2000
DOI: 10.1046/j.1365-2249.2000.01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MHC autoimmunity in Behçet’s disease: T cell responses to an HLA-B-derived peptide cross-reactive with retinal-S antigen in patients with uveitis

Abstract: SUMMARYImmune response to retinal autoantigens plays a central role in the pathogenesis of uveitis. A synthetic peptide (B27PD) from a common sequence of various HLA-B molecules associated with uveitis, such as HLA-B27 and 51, which shares amino acid homologies with a retinal-S antigen (S-Ag)-derived peptide (PDSAg), was shown to be immunogenic in human and experimental uveitis in the rat. In this study we investigated T cell responses to B27PD and PDSAg in patients with Behc Ëet's disease and posterior uveiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Development of uveitis in rats by both peptides is supportive of this model 71. T cell responses to these uveitogenic peptides were first shown in German patients with uveitis,71 and recently confirmed in a larger group of patients with BD from Turkey 74…”
Section: Retinal-s Antigen and Hla-b51—new Autoantigens?mentioning
confidence: 59%
“…Development of uveitis in rats by both peptides is supportive of this model 71. T cell responses to these uveitogenic peptides were first shown in German patients with uveitis,71 and recently confirmed in a larger group of patients with BD from Turkey 74…”
Section: Retinal-s Antigen and Hla-b51—new Autoantigens?mentioning
confidence: 59%
“…Ocular involvement commonly results in bilateral blindness despite the use of a potent immunosuppressant. Though the underlying immunopathogenic mechanisms are unclear, dysfunction of the innate and adaptive immune responses against infectious agents and autoantigens appears to be involved in the pathogenesis of Behçet uveitis [1][2][3] . We have demonstrated that the immune effectors in Behçet uveitis are distinguished from those in other causes of endogenous uveitis [4][5][6] .…”
mentioning
confidence: 99%
“…[2][3][4] Both innate and adaptive immune responses have been suggested to play a pathogenic role in Behçet's disease. 5,6 Aberrant cellular immunity, such as T-cell-mediated autoimmunity or an imbalance in the Th1/Th2 pathway, may be crucial in the pathogenesis of Behçet's disease. 7,8 Recently, CD56 ϩ T cells were reported to be higher in the aqueous humor and peripheral blood of patients with Behçet's uveitis than were other endogenous uveitides.…”
mentioning
confidence: 99%